The brand attachment and consumer behaviour in sports marketing contexts: the case of football fans in Portugal - Vieira, Carla (2020)
Sports marketing is a dynamic subject area linking academic research, marketing practitioners and public policy planners. To provide an experience that meets or exceeds a spectator’s expectations, it is important to understand consumer behaviour (e.g., behavioural intentions) and the brand attachment in specific sports marketing contexts. The main purpose of this study is to analyse how brand attachment relates to other relevant variables (brand loyalty, brand commitment, brand satisfaction, brand trust) in consumer’s behaviour applied to football fans in Portugal. The results have shown that football fans in Portugal are severely attached and loyal to their teams. The brand attachment to a football team influences all the variables included in the research conceptual model. The results also demonstrated that brand attachment, brand commitment, brand trust and brand satisfaction influence brand loyalty. A just a few studies had analysed the relation between brand attachment and other variables, so this study is groundbreaking relatively to this subject. Implications for future research are also presented.